Pendekatan Art & Letter dalam Pembelajaran Huruf Arab: Inovasi Pedagogik Guru TPQ dalam Pembelajaran Al-Qur’an - Indah Muliati; Syafei Syafei; Zilham Usral; Jamri Jamri (An-Nuha, 2026)
This study examines the improvement of TPQ teachers’ competence in Arabic letter writing through the Art & Letter approach in Nagari Kampung Batu Dalam. The study focuses on teachers’ limited ability to write hijaiyah letters proportionally, weak mastery of stroke techniques, difficulties in distinguishing similar letters, and limited use of creative approaches in Qur’anic literacy instruction. A descriptive qualitative method was employed involving 15 TPQ teachers. Data were collected through observation, in-depth interviews, practical Arabic writing tests, and documentation, and analyzed thematically to identify changes in teachers’ competencies and pedagogical experiences. The findings indicate improvements in Arabic writing skills, particularly in letter proportion accuracy, stroke control, and the ability to explain distinctions among similar hijaiyah letters. Teachers also demonstrated increased pedagogical creativity and self-confidence. This study concludes that the Art & Letter approach effectively improves the quality of Arabic letter writing instruction and strengthens Qur’anic literacy at the TPQ level.